Behind the model : a constructive critique of economic modeling - Spiegler, Peter (Cambridge : Cambridge University Press, 2015)
This ambitious book looks 'behind the model' to reveal how economists use formal models to generate insights into the economy. Drawing on recent work in the philosophy of science and economic methodology, the book presents a novel framework for understanding the logic of economic modeling. It also reveals the ways in which economic models can mislead rather than illuminate. Importantly, the book goes beyond purely negative critique, proposing a concrete program of methodological reform to better equip economists to detect potential mismatches between their models and the targets of their inquiry. Ranging across economics, philosophy, and social science methods, and drawing on a variety of examples, including the recent financial crisis, Behind the Model will be of interest to anyone who has wondered how economics works - and why it sometimes fails so spectacularly.
Title from publisher's bibliographic system (viewed on 10 Dec 2015).
Keywords: Economics; Economics -- Methodology -- Evaluation; Economics -- Mathematical models; Econometric models